Alpska politika in nevladne organizacije - Ogrin, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Protection of the Alps is an aim of many NGOs in alpine countries. Since 1991 in Slovenia relatively strong movement of civil society has developed, which contributed to the higher level of protection of alpine environment. CIPRA Slovenia is a good example of such NGO. As a part of CIPRA International, contributes its share to promotion and implemen-tation of Alpine convention.
Keywords: Alpe; Alps; ecology; ekologija; environmental protection; varstvo okolja; sustainable development; trajnostni razvoj; strategija; nevladne organizacije